DRAIVERU PLATES AR TB6560AHQ MIKROSHĒMU, DARBĪBAS IZPĒTE - Viļums, Elmārs; Pelšs, Andris; Koļčs, Guntis (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Scientific publications theme - Research of TB6560AHQ chip based stepper driver board.Work performers are Technology Academy of Rezekne, Faculty of Engineering, Second Level Professional Higher Education Bachelor's full-time study program "Mechatronics" fourth-year students Andris Pelšs, Elmārs Viļums. Scientific publications executive - Guntis Koļčs. Driver board TB6560 is designed for step motor control, it is designed for both businesses mass manufacturing of parts, as well as to private hobbies.